The Presence and Localization of G-Quadruplex Forming Sequences in the Domain of Bacteria - Bartas, Martin; Čutová, Michaela; Brázda, Václav; Kaura, Patrik; Šťastný, Jiří; Kolomazník, Jan; Coufal, Jan; Goswami, Pratik; Červeň, Jiří; Pečinka, Petr (Molecules, 2019)
The role of local DNA structures in the regulation of basic cellular processes is an emerging field of research. Amongst local non-B DNA structures, the significance of G-quadruplexes was demonstrated in the last decade, and their presence and functional relevance has been demonstrated in many genomes, including humans. In this study, we analyzed the presence and locations of G-quadruplex-forming sequences by G4Hunter in all complete bacterial genomes available in the NCBI database. G-quadruplex-forming sequences were identified in all species, however the frequency differed significantly across evolutionary groups. The highest frequency of G-quadruplex forming sequences was detected in the subgroup Deinococcus-Thermus, and the lowest frequency in Thermotogae. G-quadruplex forming sequences are non-randomly distributed and are favored in various evolutionary groups. G-quadruplex-forming sequences are enriched in ncRNA segments followed by mRNAs. Analyses of surrounding sequences showed G-quadruplex-forming sequences around tRNA and regulatory sequences. These data point to the unique and non-random localization of G-quadruplex-forming sequences in bacterial genomes.
Keywords: konformace nukleové kyseliny; Humans; G-kvadruplexy; DNA, Bacterial; Phylogeny; lidé; G-Quadruplexes; fylogeneze; Bacteria; Nucleic Acid Conformation; Genome, Bacterial; DNA bakterií; genom bakteriální